2011
DOI: 10.1159/000324147
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide as Key Mediator of Neuron-to-Neuron and Endothelia-to-Glia Communication Involved in the Neuroendocrine Control of Reproduction

Abstract: Nitric oxide (NO) is a peculiar chemical transmitter that freely diffuses through aqueous and lipid environments and plays a role in major aspects of brain function. Within the hypothalamus, NO exerts critical effects upon the gonadotropin-releasing hormone (GnRH) network to maintain fertility. Here, we review recent evidence that NO regulates major aspects of the GnRH neuron physiology. Far more active than once thought, NO powerfully controls GnRH neuronal activity, GnRH release and structural plasticity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 279 publications
(246 reference statements)
1
39
0
Order By: Relevance
“…In addition to acting directly on GnRH neurons, an increasing body of evidence suggests that kisspeptin also operates on unidentified neurons to modulate the strength of synaptic afferents and regulate GnRH secretion (Pielecka-Fortuna et al, 2008). Nitric oxide (NO), a gaseous neurotransmitter known for its important role in regulating neuronal transmission (Garthwaite, 2008) and the neuroendocrine control of reproduction (Bellefontaine et al, 2011), has recently been implicated in the regulation of GnRH neuronal activity (Clasadonte et al, 2008). This NO is produced in the vicinity of GnRH-containing perikarya by neurons expressing nNOS (Clasadonte et al, 2008), an enzyme whose activity has been shown to be tightly regulated by estrogens during the ovarian cycle in rats (d'Anglemont de Tassigny et al, 2007a;Parkash et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acting directly on GnRH neurons, an increasing body of evidence suggests that kisspeptin also operates on unidentified neurons to modulate the strength of synaptic afferents and regulate GnRH secretion (Pielecka-Fortuna et al, 2008). Nitric oxide (NO), a gaseous neurotransmitter known for its important role in regulating neuronal transmission (Garthwaite, 2008) and the neuroendocrine control of reproduction (Bellefontaine et al, 2011), has recently been implicated in the regulation of GnRH neuronal activity (Clasadonte et al, 2008). This NO is produced in the vicinity of GnRH-containing perikarya by neurons expressing nNOS (Clasadonte et al, 2008), an enzyme whose activity has been shown to be tightly regulated by estrogens during the ovarian cycle in rats (d'Anglemont de Tassigny et al, 2007a;Parkash et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus further studies will be needed to determine if these effects are directly mediated in kisspeptin neurons, or if other steroid-sensitive neurons are involved or certain chemical transmitters interact with hypothalamic neuropeptides, such as kisspeptins. In this context, an increasing body of evidence supports the idea that GnRH neurons in mammals are regulated by distinct neuronal networks and interactions via specific cell-cell signalling molecules, which may be affected by the modulatory influence of gonadal steroids (Bellefontaine et al, 2011;Prevot, 2002;Radovick et al, 2012). In mice, nitric oxide (NO) is probably involved in mediating the estrogenic positive feedback of Kiss1 onto GnRH neurons (Hanchate et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in mammals have also documented the close anatomical relationships between the Kiss1 and Gnrh-1 neurons, leading to the notion that Kiss1 neurons mediate the feedback signal from the gonad to GnRH (Bellefontaine et al, 2011;Oakley et al, 2009;Prevot, 2002;Radovick et al, 2012). However, in teleost fish, with the exception of one cichlid fish (Parhar et al, 2004), data from zebrafish (Servili et al, 2011), medaka (Kanda et al, 2012) and sea bass (Escobar et al, 2013b) all failed to confirm the presence of kiss receptors in gnrh neurons.…”
Section: Discussionmentioning
confidence: 99%
“…An additional source of pulse synchronization is in the ME, where hypophysiotropic GnRH neurons terminate within the external zone close to endothelial cells of the portal vasculature 37 . Endothelial cells in the ME might modulate GnRH release through nitric oxide secretion [38][39][40] (reviewed elsewhere 41 ). At the ME, nitric oxide is spontaneously released from an endothelial source and follows a pulsatile and cyclic pattern of secretion 38 , and inhibition of nitric oxide synthesis within the ME can disrupt reproductive cyclicity 39 .…”
Section: [H1] Gonadotroph Axismentioning
confidence: 99%